Effect of holding time on the mechanical properties and microstructural evaluation of 3Y-TZP ceramics - Golieskardi M.; Satgunam M.; Ragurajan D. (Springer International Publishing, 2023)
Ceramic materials; Doping (additives); Elastic moduli; Fracture toughness; Sintering; Vickers hardness; Yttria stabilized zirconia; Zirconia; 3Y-TZP; Ceramic samples; Holding time; Microstructural evaluation; Optimum conditions; Polycrystalline; Sintering time; Yttria stabilized tetragonal zirconias; Mechanical properties